Relatório de estágio técnico profissional em medicina veterinária: clínica médica de pequenos animais - Pinheiro, Isabela Dartora (2023)
As the last step in graduation, the veterinary medicine student goes through the professional technical internship (ETP). It is the opportunity to put into practice the theory learned over the years, and the first contact with the job market in the area chosen. In this case, the ETP was carried out at the Veterinary Hospital of the University of Passo Fundo, in the small animal medical clinic area, in the period between August 1st and October 18th, 2023, totaling 57 days and 440 hours (Appendix 1). The internship was supervised locally by Veterinary Doctor Mariana Dalla Palma and academic guidance by Veterinarian Prof. Dr. Renato do Nascimento Libardoni. During this period, the hospital's clinical routine was monitored, with scheduled clinical care, emergencies, outpatient procedures and assistance in carrying out imaging exams. Therefore, this report addresses the description of the internship location, the general activities carried out and the conditions encountered in the medical clinic during the period, divided by system and affected species. Concluding with a report on the use of erythropoietin in the treatment of anemia in a canine with chronic kidney disease. In conclusion, the importance of the professional technical internship in the training of future veterinarians has been highlighted. It is through it that the student experiences the practical routine of the profession and, with help, learns to mature the lessons learned during graduation.